The survival story of a diabetic ketoacidosis patient with blood sugar levels of 1985 mg/dL - Gopalakrishnan, Manoj; Manappallil, Robin George; Ramdas, Dipu; Jayaraj, Jishnu (Asian Journal of Medical Sciences, 2017)
No abstarct Asian Journal of Medical Sciences Vol.8(4) 2017 60-61